2006
DOI: 10.1111/j.1365-2354.2005.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Distress and coping in cancer patients: feasibility of the Icelandic version of BSI 18 and the WOC-CA questionnaires

Abstract: The aim of this study was to test the feasibility of two instruments within an Icelandic context, the Brief Symptom Inventory 18 (BSI 18) and the Ways of Coping Inventory--Cancer Version (WOC-CA) with specific focus on gender and type of treatment and coping techniques among cancer patients during time of treatment. The sample consisted of 40 cancer patients in three oncology outpatient clinics in Iceland, 53% were women and 47% men. The majority of the participants belonged to the age group 51-70. Cronbach al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
10
0
5
Order By: Relevance
“…Other studies have also shown that female patients present with higher levels of anxiety and depression (38,39). Although the mean score for levels of depression was higher in females than in males, the difference was not statistically significant ( Table 3).…”
Section: Discussionmentioning
confidence: 40%
“…Other studies have also shown that female patients present with higher levels of anxiety and depression (38,39). Although the mean score for levels of depression was higher in females than in males, the difference was not statistically significant ( Table 3).…”
Section: Discussionmentioning
confidence: 40%
“…However, in a study of Silva et al found that the coping strategy of escapeavoidance and self-control was the most used coping by patients with psoriasis and both groups present high-stress levels [26], which indicate the difference between the cultures in using ways of coping. While, in a study of Rntmsc et al distancing was the most frequently reported coping strategy [27], and men seemed to focus on the positive side more often than women did. These results indicate the importance of the coping strategies according to community and it's depending on culture or belief of people.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up interview was conducted using a coping questionnaire, which assessed information similar to that obtained at baseline. The structured questionnaire was designed according to the previous studies' questionnaires that determined coping strategies in breast cancer patients [26][27][28][29]. The content validity was confirmed using two methods (qualitative and quantitative).…”
Section: Methodsmentioning
confidence: 99%